The transnational Sowa Rigpa industry in Asia: New perspectives on an emerging economy. (January 2020) - Kloos, Stephan; Madhavan, Harilal; Tidwell, Tawni; Blaikie, Calum; Cuomu, Mingji
Abstract: This article advances the hypothesis that "traditional" Asian pharmaceutical industries are rapidly growing in size and prominence in contemporary Asia, and identifies a lack of empirical data on the phenomenon. Addressing this gap, the article provides a quantitative outline and analysis of the Sowa Rigpa (Tibetan, Mongolian and Himalayan medicine) pharmaceutical industry in China, India, Mongolia and Bhutan. Using original data gathered through multi-sited ethnographic and textual research between 2014 and 2019, involving 232 industry representatives, policy makers, researchers, pharmacists and physicians, it assembles a bigger picture on this industry's structure, size and dynamics. Revealing a tenfold growth of the Sowa Rigpa pharmaceutical industry in Asia between 2000 and 2017, the study supports its initial hypothesis. In 2017, the industry had a total sales value of 677.5 million USD, and constituted an important economic and public health resource in Tibetan, Mongolian and Himalayan regions of Asia. China generates almost 98 percent of the total sales value, which is explained by significant state intervention on the one hand, and historical and sociocultural reasons on the other. India has the second largest Sowa Rigpa pharmaceutical industry with an annual sales value of about 11 million USD, while sales values in Mongolia and Bhutan are very low, despite Sowa Rigpa's domestic importance for the two nations. The article concludes with a number of broader observations emerging from the presented data, arguing that the Sowa Rigpa pharmaceutical industry has become big enough to exert complex transformative effects on Tibetan, Mongolian and Himalayan medicine more generally. The quantitative and qualitative data presented here provide crucial foundations for further scholarly, regulatory, and professional engagement with contemporary Sowa Rigpa. Highlights: Provides the first quantitative overview of Asia's Sowa Rigpa pharmaceutical industry. Assesses the size, structure and dynamics of this industry in China, India, Mongolia and Bhutan. Shows how the industry has grown by a factor of 10 since 2000, becoming a major economic and health resource. Argues that government policies have significantly shaped development trajectories. Provides baseline data of value to researchers, industry actors and policy-makers.